2022
DOI: 10.3390/s22124584
|View full text |Cite
|
Sign up to set email alerts
|

Scan Time Reduction of PLCs by Dedicated Parallel-Execution Multiple PID Controllers Using an FPGA

Abstract: A programmable logic controller (PLC) executes a ladder diagram (LD) using input and output modules. An LD also has PID controller function blocks. It contains as many PID function blocks as the number of process parameters to be controlled. Adding more process parameters slows down PLC scan time. Process parameters are measured as analog signals. The analog input module in the PLC converts these analog signals into digital signals and forwards them to the PID controller as inputs. In this research work, a fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The shortest execution times T E , along with the smallest resource usage, were reported by Sreenivasappa and Udaykumar [37]. Similar results were obtained by Dhanabalan et al [25]. The actual calculations are carried out with combinatorial structures capable of generating the result in one clock cycle.…”
Section: Implementation Of the Proposed Circuitsupporting
confidence: 76%
See 3 more Smart Citations
“…The shortest execution times T E , along with the smallest resource usage, were reported by Sreenivasappa and Udaykumar [37]. Similar results were obtained by Dhanabalan et al [25]. The actual calculations are carried out with combinatorial structures capable of generating the result in one clock cycle.…”
Section: Implementation Of the Proposed Circuitsupporting
confidence: 76%
“…Although the implementation of the PID algorithm in FPGA devices is described in many research papers, only some of them deal directly with the circuit microarchitecture, i.e., how the digital circuit is made up of its hardware components. These include the studies reported in [21,25,32,36,37,[39][40][41][42][43]. The same functionality can be implemented in a digital circuit following various structural schemes.…”
Section: Motivationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, we present the implementation of controller using dedicated Field Programmable Gate Arrays (FPGA) design to calculate the response values of the controller. The FPGA-based designs to calculate the response of PID controllers are present in various fields like motion control systems 24 , respiratory systems 25 or industrial PLC controllers 26 . Among currently existing solutions, there are also already taken attempts to implement a fractional-order controller with FPGA 27 .…”
Section: Introductionmentioning
confidence: 99%